A tribute to Giovanni Anania: Scholar, Mentor, Friend - , (Bio-based and Applied Economics, 2015)
This section collects several contributions intended to offer a tribute to Giovanni Anania. Giovanni suddenly and unexpectedly passed away on 15 July 2015. This section is based on the contributions to the special session chaired by Jo Swinnen - held at the 29th International Conference of Agricultural Economics, Milan, 9-14 August 2015 - to honor the memory and contribution of Giovanni Anania.